Investigating factors that affect survival of horses following treatment for synovial sepsis - de Souza, Therese (2023)
Synovial sepsis is a major cause of death and loss of function in horses. Despite appropriate treatment there are cases that have persistent infections posing a welfare issue to horses. This thesis presents research identifying factors associated with outcomes.